Report on Paddy Mitra Chatbot Pilot Testing - Bharti, Preeti; Gakhar, Shalini; Patnaik, Girija Prasad (International Rice Research Institute, 2025)
PaddyMitra stands for Precision Advisory for Data-Driven Yield Management of Irrigation, Timing, and Resource Application. This pilot study was designed to assess the feasibility and farmers' experience using the PaddyMitra chatbot in the Puri and Balasore districts of Odisha. Specifically, the study aimed to: • Understand the digital readiness and demographic characteristics of rice farmers, • Assess how farmers perceive and use the chatbot’s nutrient recommendations, and • Capture feedback for future improvements, including additional advisory modules.